Poetic figures of Meaning in the Rhetorical Works of 'Abd al- QÄhir al-JurjÄnÄ« - Buthayna Sulaymān (دراسات فی اللغه العربیه و آدابها)
Â Â  This study, which is done in the light of modern research, is a small step in exploring the great heritage of Arabic rhetoric. It may be quite appropriate to explore rhetorical techniques in the work of 'Abd al- QÄhÄ«r al-JurjÄnÄ«, particularly because he has been neglected in many pieces of research on rhetoric. This article is an attempt for describing 'Abd al- QÄhÄ«râs approach in investigating novel rhetorical techniques and creative use of figures of meaning and tropes in Arabic poetry based on âcomposition theoryâ.